Do Mandatory Pensions Decrease Household Savings? Evidence for the Netherlands - Rob Euwals (Institute for the Study of Labor (IZA), 2000)
The Dutch mandatory pension system consists of two parts: a public pay-as-you-go part that provides a minimum income to all Dutch inhabitants over age 64; and an occupation-specific capital-funded part that provides supplementary retirement income. The goal of this paper is to test for the effect of mandatory pensions on discretionary household savings. The data are drawn from the CentER Savings Survey, which consists of a representative and a highest-income-decile sample of Dutch households. The survey contains rich information on house-hold wealth, pension rights and savings attitudes. A result of the empirical analysis is that the impact of the public part of the Dutch pension system is not well identified. The occupational pensions have a significant negative impact on savings motives with respect to old age. Concerning the effect on household wealth, evidence is mixed. Only in the highestincome- decile sample there is evidence for a significantly negative impact of occupational pensions.
Keywords: H55; D91; C21; 330; Savings; pensions; life cycle hypothesis; Sparen; Einkommenshypothese; Alterssicherung; Gesetzliche Rentenversicherung; Versicherungspflicht; Schätzung; Niederlande